Efficacy and Safety of Low-Dose Everolimus as Maintenance Immunosuppression in Cardiac Transplant Recipients. (17th April 2012) - Fuchs, Uwe; Zittermann, Armin; Schulz, Uwe; Gummert, Jan F.
Abstract : For cardiac transplant (CTx) recipients, the recommended everolimus (EVL) dose is 0.75 mg bid or 1.5 mg bid and the target trough blood level is 3–8 μg/L. We studied a cohort of 56 CTx patients with chronic kidney disease receiving 0.75 mg bid EVL to maintain blood levels of 5–8 ug/L (designated RD group) and a cohort of 51 CTx patients with chronic kidney disease receiving 0.5 mg bid to maintain blood levels of 3–5 ug/L (designated LD group). The primary endpoint was a composite of death, rejection and premature EVL discontinuation up to 1 year after introduction of EVL. The primary endpoint was reached by 32% of patients in the LD group and by 41.1% of patients in the RD group (P = 0.361 ). Biochemical safety parameters were comparable in both groups. Our results indicate that low-dose EVL may be as effective and safe as regular dose EVL.